Hierarchical on-surface synthesis and electronic structure of carbonyl-functionalized one- and two-dimensional covalent nanoarchitectures - Steiner, Christian; Gebhardt, Julian; Ammon, Maximilian Michael; Yang, Zechao; Heidenreich, Alexander; Hammer, Natalie; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nature Communications, 2017)
The fabrication of nanostructures in a bottom-up approach from specific molecular precursors offers the opportunity to create tailored materials for applications in nanoelectronics. However, the formation of defect-free two-dimensional (2D) covalent networks remains a challenge, which makes it difficult to unveil their electronic structure. Here we report on the hierarchical on-surface synthesis of nearly defect-free 2D covalent architectures with carbonyl-functionalized pores on Au(111), which is investigated by low-temperature scanning tunnelling microscopy in combination with density functional theory calculations. The carbonyl-bridged triphenylamine precursors form six-membered macrocycles and one-dimensional (1D) chains as intermediates in an Ullmann-type coupling reaction that are subsequently interlinked to 2D networks. The electronic band gap is narrowed when going from the monomer to 1D and 2D surface-confined π-conjugated organic polymers comprising the same building block. The significant drop of the electronic gap from the monomer to the polymer confirms an efficient conjugation along the triphenylamine units within the nanostructures.

Host guest chemistry and supramolecular doping in triphenylamine-based covalent frameworks on Au(111) - Steiner, Christian; Fromm, Lukas; Gebhardt, Julian; LIU, YI; Heidenreich, Alexander; Hammer, Natalie; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nanoscale, 2021)
The post-synthetic modification of covalent organic frameworks (COFs) via host-guest chemistry is an important method to tailor their electronic properties for applications. Due to the limited structural control in the assembly of two-dimensional surface-supported COFs, supramolecular networks are traditionally used at present for host-guest experiments on surfaces, which lack structural and thermal stability, however. Here, we present a combined scanning tunneling microscopy and density functional theory study to understand the host-guest interaction in triphenylamine-based covalently-linked macrocycles and networks on Au(111). These triphenylamine-based structures feature carbonyl and hydrogen functionalized pores that create preferred adsorption sites for trimesic acid (TMA) and halogen atoms. The binding of the TMA through optimized hydrogen-bond interactions is corroborated by selective adsorption positions within the pores. Band structure calculations reveal that the strong intermolecular charge transfer through the TMA bonding reduces the band gap in the triphenylamine COFs, demonstrating the concept of supramolecular doping by host-guest interactions in surface-supported COFs. Halogen atoms selectively adsorb between two carbonyl groups at Au hollow sites. The mainly dispersive interaction of the halogens with the triphenylamine COF leads to a small downshift of the bands. Most of the halogens change their adsorption position selectively upon annealing near the desorption temperature. In conclusion, we demonstrate evidence for supramolecular doping via post-synthetic modification and to track chemical reactions in confined space. This journal is
CRIS-Team Scopus Importer:2021-06-18

Long-range energy transport in single supramolecular nanofibres at room temperature - Haedler, Andreas T.; Kreger, Klaus; Issac, Abey; Wittmann, Bernd; Kivala, Milan; Hammer, Natalie; Koehler, Juergen; Schmidt, Hans-Werner; Hildner, Richard (Nature, 2015)
Efficient transport of excitation energy over long distances is a key process in light-harvesting systems, as well as in molecular electronics. However, in synthetic disordered organic materials, the exciton diffusion length is typically only around 10 nanometres (refs 4, 5), or about 50 nanometres in exceptional cases, a distance that is largely determined by the probability laws of incoherent exciton hopping. Only for highly ordered organic systems has the transport of excitation energy over macroscopic distances been reported–for example, for triplet excitons in anthracene single crystals at room temperature, as well as along single polydiacetylene chains embedded in their monomer crystalline matrix at cryogenic temperatures (at 10 kelvin, or -263 degrees Celsius). For supramolecular nanostructures, uniaxial long-range transport has not been demonstrated at room temperature. Here we show that individual self-assembled nanofibres with molecular-scale diameter efficiently transport singlet excitons at ambient conditions over more than four micrometres, a distance that is limited only by the fibre length. Our data suggest that this remarkable long-range transport is predominantly coherent. Such coherent long-range transport is achieved by one-dimensional self-assembly of supramolecular building blocks, based on carbonyl-bridged triarylamines, into well defined H-type aggregates (in which individual monomers are aligned cofacially) with substantial electronic interactions. These findings may facilitate the development of organic nanophotonic devices and quantum information technology.
EAM Import::2019-03-12

N-Heterotriangulenes: Fascinating Relatives of Triphenylamine - Hammer, Natalie; Schaub, Tobias; Meinhardt, Ute; Kivala, Milan (Chemical Record, 2015)
Carbonyl- and dimethylmethylene-bridged triphenylamines called N-heterotriangulenes are not only aesthetically pleasing extgreekp-conjugated scaffolds interesting on their own but also provide numerous possibilities for further synthetic modifications to serve as versatile precursors for the construction of functional organic molecules. In this Personal Account we give a historical synopsis depicting the long way from the initial synthesis of N-heterotriangulenes back in the 1970s to their derivatization followed by recent applications in organic electronics. As a part of our ongoing research on heteroatom-doped extgreekp-conjugated scaffolds we provide an overview of our synthetic efforts involving the N-heterotriangulene scaffolds and discuss the optoelectronic, redox, and self-assembly properties of the resulting molecular entities.
EAM Import::2019-03-12

Synthesis and Photophysical Properties of Multichromophoric Carbonyl-Bridged Triarylamines - Haedler, Andreas T.; Beyer, Sebastian R.; Hammer, Natalie; Hildner, Richard; Kivala, Milan; Koehler, Juergen; Schmidt, Hans-Werner (Chemistry - A European Journal, 2014)
The synthesis and photophysical properties of two novel multichromophoric compounds is presented. Their molecular design comprises a carbonyl-bridged triarylamine core and either naphthalimides or 4-(5-hexyl-2,2'-bithiophene)naphthalimides as second chromophore in the periphery. The lateral chromophores are attached to the core via an amide linkage and a short alkyl spacer. The synthetic approach demonstrates a straightforward functionalization strategy for carbonyl-bridged triarylamines. Steady-state and time-resolved spectroscopic investigations of these compounds, in combination with three reference compounds, provide clear evidence for energy transfer in both multichromophoric compounds. The direction of the energy transfer depends on the lateral chromophore used. Furthermore, the compound bearing the lateral 4-(bithiophene)naphthaimides is capable of forming fluorescent gels at very low concentrations in the sub-millimolar regime whilst retaining its energy transfer properties.
EAM Import::2019-03-12

Synthesis and Properties of Arylvinylidene-Bridged Triphenylamines - Hammer, Natalie; Shubina, Tatyana; Gisselbrecht, Jean-Paul; Hampel, Frank; Kivala, Milan (Journal of Organic Chemistry, 2015)
A series of arylvinylidene-bridged triphenylamines were efficiently synthesized through the thionation/Barton-Kellogg olefination sequence from their corresponding carbonyl precursors. The electrochemical investigations identified these highly distorted scaffolds as fairly strong electron donors capable of several reversible oxidation steps with the first oxidation occurring at a potential comparable to that of ferrocene for the n-hexyl-substituted diphenylvinylidene-bridged compound.
EAM Import::2019-03-12

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics